The Titan's curse - Riordan, Rick. (New York : Scholstic, 2008)
The disappearance of the goddess Artemis while out hunting a rare, ancient monster, prompts a group of her followers to join Percy and his friends in an attempt to find and rescue her before the winter solstice, when her influence is needed to sway the Olympian Council regarding the war with the Titans.
4.7
5-8
Keywords: Mythology, Greek -- Juvenile fiction; Artemis (Greek deity) -- Juvenile fiction; Animals, Mythical -- Juvenile fiction; Monsters -- Juvenile fiction; Titans (Mythology) -- Juvenile fiction; Mythology, Greek -- Fiction; Animals, Mythical -- Fiction; Monsters -- Fiction; Fantasy; Greek mythology -- Fiction; Mythical animals -- Fiction; Monsters -- Fiction; Fantasy fiction; Fantasy fiction